離型剤分散液の製造方法、離型剤分散液及びそれを用いたトナーの製造方法 (2015)
PROBLEM TO BE SOLVED: To provide a method for manufacturing a release agent dispersion containing efficiently uniform release agent particles with small particle size; and to provide a toner for image formation capable of obtaining an excellent image over a long term using the obtained release agent dispersion by the method. SOLUTION: The method for manufacturing the release agent dispersion characterized by containing the following steps: a step of dissolving or dispersing at least a release agent in a supercritical fluid or a subcritical fluid to obtain a composition; and a step of ejecting the composition in a liquid medium, rapidly expanding it and depositing it to obtain the release agent dispersion where release agent particles are dispersed. There is also provided a toner using the obtained release agent dispersion by the method for manufacturing the release agent dispersion. COPYRIGHT: (C)2011,JPO&INPIT